Review of Mendelian randomization studies on common male-specific diseases - Pang, Qixin; Chang, Zhe; Liu, Hao; Chen, Jianshe; Ma, Sicheng; Zhang, Chenming; Sun, Zixue (Frontiers in Endocrinology, 2025)
Although numerous Mendelian randomization studies on risk factors have been conducted in male medicine, a systematic synthesis of these findings is still lacking. This review searched relevant literature in PubMed and the Web of Science published before May 2024; systematically summarized the progress in the application of Mendelian randomization in male infertility, erectile dysfunction, prostate cancer, and prostatitis; summarized and classified the risk factors affecting men’s health, such as the gut microbiota, modifiable risk factors and related diseases; and presented some problems and solutions that were presented in these studies. This information offers valuable insights into the etiology and pathogenesis of male-specific diseases.